Strategic partnership of the university: the principles of formation and development - Nadezhda D. Guskova; Irina N. Krakovskaya (Высшее образование в России)
The concept of development of higher education in partnership with the state, society and business is under active formation. The article suggests the classification of principles of strategicpartnership of higher education institutions, taking into account the general rules on management of multilateral partnerships and features of interaction with partners in universities.